PERANCANGAN GAME EDUKASI SEBAGAI MEDIA PEMBELAJARAN BERBASIS MOBILE MENGGUNAKAN ALGORITMA FISHER-YATES DAN FLOOD FILL - Rifky Syaifulloh (KLIK- KUMPULAN JURNAL ILMU KOMPUTER, 2021)
Information technology is currently increasingly developing, especially on smartphone devices. The reason various users use smartphone devices is their practical size and of course their portability. Smartphone devices can also be a learning medium in the form of games or games, one of which is games for children's education. The problem that often occurs in children in the way of learning is that it is easy to develop boredom if the child is only encouraged by learning material without any entertainment or games. This game is designed to change the way of learning, especially in early childhood between the ages of 3 to 6 years. This mobile-based game is made using the App Inventor with an interactive and attractive display to learn to recognize numbers, fruit, letters, animals, vegetables and colors as well as quiz questions. In this educational game that was made, it was designed using the Rapid Application Development (RAD) method as a completion stage starting from the planning stage to the implementation stage of the program. This educational game also applies the Fisher-Yates algorithm to randomize questions. The results of this study show 10 quiz questions randomly from 15 existing questions, and apply the Flood Fill algorithm for coloring objects or images. With the design of games for mobile-based education, it is hoped that it can make children's brains more active and creative during their growth period and help children's learning processes in order to increase their broader knowledge.Keyword: App Inventor, Fisher Yates, Flood Fill, Education Game, RAD Teknologi informasi pada saat ini semakin hari semakin berkembang, khususnya pada perangkat smartphone. Alasan dari berbagai pengguna menggunakan perangkat smartphone adalah ukurannya yang praktis dan tentunya mudah dibawa. Perangkat smartphone juga bisa menjadi media pembelajaran dalam bentuk permainan atau game, salah satunya adanya game untuk edukasi anak. Permasalahan yang kerap terjadi pada anak dalam cara belajar yaitu mudah timbulnya kebosanan jika anak hanya didorongkan oleh materi pembelajaran saja tanpa adanya hiburan atau permainan. Dirancangnya game ini untuk mengubah cara belajar khususnya pada anak usia dini antara umur 3 sampai 6 tahun.  Pada game berbasis mobile ini dibuat menggunakan App Inventor dengan tampilan yang interaktif dan menarik  untuk belajar mengenal angka, buah, huruf, hewan, sayur dan warna serta adanya soal kuis. Pada game edukasi ini yang dibuat ini dirancang menggunakan metode Rapid Application Development (RAD) sebagai tahapan penyelesaian mulai dari tahap perencanaan sampai tahap implementasi dari program. Pada game edukasi ini juga menerapkan  algoritma Fisher-Yates untuk melakukan pengacakan soal. Pada hasil penelitian ini ditampilkan 10 soal kuis secara acak dari 15 soal yang ada, serta menerapkan algoritma  Flood Fill untuk pewarnaan objek atau gambar. Dengan dirancangnya game untuk edukasi berbasis mobile ini diharapkan dapat membuat otak anak lebih aktif dan kreatif dimasa pertumbuhannya serta membantu proses belajar anak agar dapat menambah pengetahuan yang lebih luas.Kata kunci: App Inventor, Fisher Yates, Flood Fill, Game Edukasi, RAD